Digital Financial Reporting: Analysis of the Quality of Cyber Security Visualization and Disclosure in Investor Relations of Government Banks - ANDHIKA, I Putu Indra; JAYANTIKA, I Nyoman Satya Prawira; PUTRA, Anak Agung Bagus Surya Adi; PERKASA, Gede Anantavijaya Satria (Journal of Social Sciences and Cultural Study, 2025)
This research analyzes the financial report visualization and corporate cybersecurity risk management of four leading Indonesian state-owned banks: Bank Rakyat Indonesia (BRI), Bank Negara Indonesia (BNI), Bank Tabungan Negara (BTN), and Bank Mandiri, during the period of 2022 to 2024. The research indicates that these four banks consistently demonstrate strong financial performance, characterized by solid growth in net profit, loans, and third-party funds. This growth is driven by aggressive digital transformation strategies and a focus on specific market segments, supported by maintained asset quality and a stable funding base. In terms of cybersecurity risk management, all banks show a strong commitment through the adoption of international frameworks (such as NIST and ISO 27001), the establishment of dedicated security units (CISO, CSIRT), and collaboration with the National Cyber and Crypto Agency (BSSN). Nevertheless, the level of transparency in public disclosure regarding cybersecurity policies and architecture details varies among the banks. Overall, these banks exhibit robust financial health and an increasingly mature cybersecurity posture, yet there are opportunities to enhance financial report visualization and cybersecurity disclosure transparency to strengthen investor confidence and operational resilience.